PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL COOPERATIVE LEARNING TIPE THINK TALK WRITE DI KELAS IV SDN 05 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Ivo Gayatri; Ivo Gayatri; Melva Zainil; Yanti Fitria (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research  was  to improved the learning outcomes of student in Social Science Knowledge  used  Think Talk Write on 4th   grade elementary school. Types of this research were 25 people. The implementation of this research was conducted in two cycles with   research   procedure   that   consist   of   planning,   implementation, observation and reflectio. The results showed an increase in terms of (a) the RPP of cycle I with an average of 78,22% to 92,8% in cycle II, (b) Implementation teacher’s activity cycle I with an average 81,25% to 96,8% in  cycle II,  while for the implementationon the students cycle I  with  an average 81,25% to 96,8% in cycle II, (c) Students learning outcomes in cycle I with an average of 77 be 87,3 in cycle II. It can be concluded that used Think Talk Write  model can improve students achievement in Social Science Knowledge of 4th grade elementary school at SDN 05 2x11 enam lingkung kabupaten Pdang Pariaman.Keyword : Learning outcomes, mathematic, TTW